PENINGKATAN HASIL BELAJAR MENGGUNAKAN MEDIA PETA KONSEP DI SD - Istikholah; Aries Tika Damayani; Sukamto; Siti Sumarmi (STKIP Subang, 2023)
Based on the learning outcomes of fourth grade students of SD Negeri Sampangan 02, there is a decrease in learning outcomes in IPAS learning. The decrease in the learning outcomes of grade IV students in IPAS lessons is because it is still a new thing for them. This happens because class IV is the class that is the target of the first stage in implementing the independent curriculum. The researcher's aim is to focus on classroom action research which aims to improve students' IPAS learning outcomes through concept map media. The improvement of IPAS learning outcomes using concept map media at SD Negeri Sampangan 02 in the 2022/2023 academic year has increased, this can be seen from the learning outcomes in cycles I and II, data obtained that student learning outcomes have increased. The results of the first cycle test obtained as many as 13 students or 46.43% were complete and 15 students or 53.57% were not complete. Then in the second cycle test results showed 22 students or 78.57% complete and 6 students or 21.43% not complete. With the improvement that occurred in students who had reached 78.57% of students had completed and exceeded 75% of the success indicators, it was stated that this learning improvement had been successful.